A highly directive array of nature‐inspired based patch antennas. Issue 8 (10th May 2022) - Kola, Kalyan Sundar; Chatterjee, Anirban
Abstract: A Ku‐band satellite application‐based printed planar array is conferred in this article. The proposed array's sole radiator design is inspired by the essence and based on a nature‐inspired flower. The solitary element offers enormous directivity and insignificant cross‐polarization (x‐pol.) level in the half‐power beam‐width (HPBW) portion of the main beam's path. Networks within the array are built to have low loss and fast bandwidth response times for the corporate feed network. The sole antenna has a very high gain and a substantial impedance bandwidth of 11.52 dBi and 528 MHz, respectively, and resonates at 17.96 GHz. The array produces 16.83 dBi gain and 764 MHz impedance bandwidth at the resonant frequency of 17.97 GHz. In the direction of the primary beam's propagation, the prototyped array delivered −42 dB of measured x‐pol. level. For evaluating the prototypes' electromagnetic compatibility (EMC), the derived correction factors (CF) are 42.54 and 39.56 dB/m, respectively. In addition, the proposed prototypes have good radiation efficiency of 92% and 90%, respectively. The measured result of the prototype is quite comparable to that of its modeled equivalent.